Evaluation of the chemical consistency of Yin‐Chen‐Hao‐Tang prepared by combined and separated decoction methods using high‐performance liquid chromatography and quadrupole time‐of‐flight mass spectrometry coupled with multivariate statistical analysis. Issue 9 (8th March 2019) - Tian, Qiang; Liu, Fang; Xu, Zhou; Liu, Huan; Yin, Hao; Sun, Zhaolin; Chen, Mingcang; Li, Zhixiong; Ma, Lin; Huang, Chenggang
Abstract: In this study, Yin‐Chen‐Hao‐Tang prepared by two decoction methods, namely, combined decoction (modern decoction method) and separated decoction (traditional decoction method), was analyzed by high‐performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry. The acquired datasets containing sample codes, tR ‐ m/z pairs and ion intensities were processed with multivariate statistical analyses, such as principal component analysis and an orthogonal partial least squared discriminant analysis model, to globally compare the chemical differences between the different decoction samples. Then, the chemical differences between the combined and separated decoctions were screened out by S‐plots generated from the orthogonal partial least squared discriminant analysis model and compared with chemical information from an established in‐house library. The six components that contributed the most to the chemical differences were identified as chlorogenic acid, caffeic acid, geniposide, genipin, scopoletin, and 3, 5‐dicaffeoylquinic acid. The concentrations of genipin and caffeic acid from the separated decoction were higher than those from the combined decoction, indicating that the separated decoction may present a stronger hepatoprotective effect. However, the results still require further investigation through pharmacological and clinical studies. Our findings not only establish a strategy to evaluate chemical consistency of Yin‐Chen‐Hao‐Tang but also provide the scientific basis for using traditional separated decoction method.